العقيدة الإلهية في الفكر العربي - جفال، نور الدين Jaffal, Nouruldin; باهي، التركي (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2022)
يلاحظ من خلال العديد من الدراسات الدينية والاجتماعية والأنثروبولوجية أن العقيدة الإلهية في المجتمعات عموما والمجتمعات العربية خصوصا، وجدت مع وجود الإنسان ذاته، أي منذ وجود آدم عليه السلام، ثم طرأت عليها عدة تغيرات وتصورات وخرجت عن مدلولها الأول في الكثير من المجتمعات البشرية بما فيها المجتمعات العربية، وكان تصحيح مسارها عن طريق الأنبياء والرسل، والواقع المعاصر يظهر تلك التغيرات ويظهر كذلك العقيدة الإلهية كما جاء بها خاتم الأنبياء عليه الصلاة والسلام في المجتمع العربي خصوصا والمجتمع العالمي عموما. It is noted through many religious, social and anthropological studies that the divine belief in societies in general and Arab societies in particular, existed with the existence of man himself, that is, since the existence of Adam, peace be upon him, and then several changes and perceptions occurred to it and departed from its first meaning in many human societies, including societies Arabic, and its course was corrected by the prophets and messengers, and the contemporary reality shows these changes and also shows the divine doctrine as brought by the Seal of the Prophets, peace and blessings be upon him, in the Arab community in particular and the global community in general.
Keywords: الظواهر الدينية -- الأديان السماوية -- الفكر العربي